Product and furniture design - Thompson, Rob. (London : Thames & Hudson, 2011)
1: FORMING TECHNOLOGY -- Compression molding -- Thermoforming -- Rotation molding -- Plastic extrusion -- Injection molding -- Metal injection molding -- Foam molding -- Dip molding -- High pressure die casting -- Investment casting -- Metal press forming -- Punching and blanking -- Metal spinning -- Tube and section bending -- Swaging -- Superplastic forming -- Ceramic press molding -- Ceramic slip casting -- CNC machining -- Loom weaving -- Laser cutting ##2: JOINING TECHNOLOGY -- Hot plate welding -- Ultrasonic welding -- Vibration welding -- Staking -- CNC joinery -- Assembly -- Upholstery ##3: FINISHING TECHNOLOGY -- Tampo printing -- Screen printing -- Anodizing -- Automated spray painting -- Electroplating -- Vacuum metalizing.
Includes index.
boek